Perbandingan Hasil Belajar Mahasiswa Prodi Pendidikan Bahasa Jepang dan Sastra Cina Angkatan 2015 Universitas Brawijaya - Sutiyarti, Ulfah; Wulan, Diah Ayu; Saragih, Febi Ariani; Widyaningsih, Galih Edy Nur (Journal of Japanese Language Education and Linguistics, 2018)
This study aims to determine differences in the acquisition of learning outcomes of stu-dents of Japanese Language Education and Chinese Literature Class of 2015 in GPA based on the type of college entrance selection. This research used ex post facto type (examine the circumstances that have happened), and also this study only see student learning outcomes from college entrance, and do not see the learning process of each study program. The results of the study are expected to be considered in determining the quota of student admission selection path. This research is a quantitative descriptive study with research subjects of students of Japanese Language Education and Chinese Literature Class of force of 2015. Data collection technique using documentation technique is KHS student. Data analysis was performed by: 1) Assumption test using data normality test and homogeneity test, 2) One way ANOVA analysis. The results of the study show that the Chinese Literature Study achievement of independent students has a GPA not much different from the SNMPTN and SBMPTN lines. Meanwhile, in the Japanese Education Education Program, students from independent pathways under SBMPTN defeat stu-dentsâ€™ IPK score of SNMPTN. So it can be concluded that college entrance is still not able to guarantee student achievement in college. Interest and attention will result in learning motivation and successful desire in students is the main capital to achieve the highest achievement in collegesuccessful desire in students is the main capital to achieve the highest achievement in collegeÂ Â